COMPARISON OF THE PSYCHOMOTOR PROFILE BETWEEN CHILDREN FROM 4 TO 5 YEARS OLD IN 2 PRIVATE SCHOOLS (Fiep Bulletin - online, 2014)
This research verified the psychomotor development from 4 to 5 years old in both genders, from 2 private schools. The first school developed a psychomotor work with the children in physical education classes, once a week; the second school didn't have any physical education classes inserted on preschoolers.To identify the deficiencies in psychomotor areas in children from 4 to 5 years old, with the objective to verify if the physical education directed to psychomotoricity offers great possibilities of success.The research is a transverse one, and it was realized in the city of Anápolis-GO, in two private schools. The totality of valuated children was 31 (from 4 to 5 years of age), from genders, 19 boys and 12 girls. There were 8 boys and 8 girls on the first school and 11 boys and 4 girls on the second school. In one of the schools, the physical education teacher worked the psychomotoricity in specific classes once a week, during 45 minutes and there wasn't any work of this kind on the other school. The first school obtained the best performance than the second school in all factors of the battery, which are: tonicity, equilibration, lateralization, body notion, space-time structures, global praxis and thin praxis. It is concluded that on the school where children have physical education once a week, on which they have a development of their psychomotor areas, these children are more developed in all the factors of the PMB, of Fonseca, 1995, than the other children from the other school. So, the physical education has possibilities to develop the psychomotor dimension of people, especially on kids and it is of great importance in preschoolers learning.
Keywords: Psychomotor Battery; children; profile psychomotor